Modified diamond nanosheet epoxy anticorrosive composite material as well as preparation method and application thereof
By combining rare earth cerium salt-modified two-dimensional diamond nanosheets with epoxy resin, a modified diamond nanosheet epoxy composite material is formed, which solves the problem of insufficient corrosion resistance of epoxy resin coating in corrosive environments, and achieves a significant improvement in the corrosion resistance and protection effect of the coating.
Patent Information
- Application Number
- CN202411926598.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-04-01
AI Technical Summary
When existing epoxy resin coatings are used in corrosive environments for a long time, gas permeability and structural defects lead to insufficient anti-corrosion performance, which cannot effectively block the penetration of corrosive media.
The modified two-dimensional diamond nanosheets are combined with epoxy resin by combining the rare earth cerium salt to form a modified diamond nanosheet epoxy composite material. The material uses cerium ions to form hydrogen bonds and cation-π interactions with functional groups on the surface of diamond nanosheets, enhancing the physical barrier and corrosion inhibition capabilities of the coating.
It significantly improves the corrosion resistance and protection of the coating, extends the service life of the composite material, and maintains good bonding between the epoxy resin and the substrate.
Smart Images

Figure CN119735917A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of anti-corrosion materials, and in particular to a modified diamond nanosheet epoxy anti-corrosion composite material and a preparation method and application thereof. Background Art
[0002] Corrosion, as the main cause of material performance degradation, refers to the process in which materials gradually lose their original properties under the erosion of environmental media such as air and water. The corrosion of metal materials not only leads to huge losses of resources and energy, but also causes serious economic burdens, product pollution and over-design, and more potentially threatens safety. By taking effective protective measures, 25% to 40% of such losses can be avoided in theory. Therefore, exploring and implementing efficient anti-corrosion strategies is of vital importance to promoting the sustainable development of the engineering industry.
[0003] Among the existing anti-corrosion methods, organic protective coatings stand out for their wide applicability and high cost-effectiveness, becoming an important line of defense to protect metal materials from corrosion. However, traditional organic coatings, especially solvent-based coatings, release a large amount of volatile organic compounds (VOCs) during the preparation and application process, posing a threat to the environment and human health. With the improvement of environmental awareness and strict regulations, environmentally friendly coatings have gradually become the mainstream of the market. Among them, organic powder coatings have been rapidly promoted and applied in many fields due to their zero VOC emissions, high utilization rate, excellent coating performance, eco-friendly and economical performance (i.e., 4E advantages).
[0004] Although organic epoxy resin coatings play an important role in metal corrosion protection due to their chemical stability, good mechanical properties and excellent adhesion, their inherent gas permeability (pore diameter is usually 10 -5 ~10 -7 , which is larger than the molecular diameter of H2O and O2 (10 -10 )) and structural defects such as holes and cracks that may occur in long-term use still limit its anti-corrosion performance. Especially when the coating is in a corrosive environment for a long time, O2, H2O and Cl - The penetration of corrosive media such as paint will accelerate the damage and peeling of the coating, thereby weakening its protective effect.
[0005] Studies have shown that the addition of zinc powder to epoxy powder coatings can effectively enhance the corrosion protection capabilities of the coatings by relying on the sacrificial anodic protection mechanism of metallic zinc and the dense corrosion products formed. However, the amount of zinc powder added needs to be carefully controlled. Once it exceeds 40%, it will significantly weaken the adhesion and anti-corrosion properties of the coating. For water-based epoxy zinc-rich coatings, researchers generally believe that the amount of zinc powder added must reach more than 80% in order to fully exert its sacrificial anodic protection, but this is obviously not an ideal solution for optimizing the anti-corrosion performance of epoxy powder coatings.
[0006] To address this problem, scientists have begun to explore new ways to incorporate nanofillers into polymer powder coatings, aiming to improve their permeability resistance and corrosion resistance. Among the many nanofillers, carbon nanofillers stand out for their ultra-low density and excellent reinforcement effect. It is worth noting that even at extremely low addition levels (less than 1%), carbon nanofillers can significantly improve the anti-corrosion performance of the coating, showing great application potential. At the same time, the scientific and industrial communities have also shown great interest in incorporating flake fillers (such as mica iron oxide, glass flakes, etc.) into resin powder coatings, hoping to further improve the permeability resistance and corrosion resistance of the coating. The proportion of flake fillers in the coating plays a vital role in the overall performance of the coating. However, due to their large thickness, traditional flake fillers often require a high proportion (more than 20%) and a thick coating (greater than 400μm) to achieve the ideal barrier effect, but this increases the risk of structural defects such as pores and voids in the coating. These defects are like hidden dangers in the coating, which may cause the coating to blister, crack, and even eventually fail due to corrosion, seriously affecting the service life and protective effectiveness of the coating. Therefore, how to effectively reduce the risk of structural defects while ensuring coating performance has become a top priority in current research.
[0007] Diamond nanosheet materials, with their high mechanical strength, excellent chemical stability, high wear resistance and high aspect ratio, have become highly promising anti-corrosion additives. Patent application document CN118048061A discloses a method for preparing a fluorinated diamond nanosheet anti-corrosion coating by modifying diamond nanosheets with a perfluorosilane coupling agent. The method successfully prepares a diamond nanosheet anti-corrosion coating with fluorinated properties by modifying diamond nanosheets with a perfluorosilane coupling agent. It not only has good anti-corrosion performance, but also incorporates temperature control and self-healing functions, aiming to improve the maintenance convenience of the coating in practical applications. However, the use of fluorine reagents may cause environmental problems, which is a consideration that cannot be ignored in the current environmental protection situation. Secondly, although the FC bonds added during the modification process give the coating specific fluorination properties, they may also weaken the bonding force between the coating and the substrate. The introduction of FC bonds may change the chemical properties of the coating surface, resulting in a weakening of the interaction between the coating and the substrate, which in turn affects the overall performance and durability of the coating.
[0008] Therefore, developing a new, environmentally friendly and efficient epoxy resin-based anti-corrosion material, combined with the advantages of high-performance additives such as diamond nanosheets, has become a direction that needs to be studied in depth. This is not only of great significance for improving the anti-corrosion performance of metal materials, but also can promote the coating industry to move towards green transformation and sustainable development. However, there are no related reports yet. Summary of the invention
[0009] The present invention aims to solve at least one of the technical problems existing in the prior art. To this end, the present invention provides a modified diamond nanosheet epoxy composite material, which has a durable and excellent anti-corrosion performance.
[0010] The invention also provides a method for preparing the composite material.
[0011] The invention also proposes application of the composite material.
[0012] The modified diamond nanosheet-epoxy composite material according to the first embodiment of the present invention comprises the following raw materials: modified diamond nanosheets and epoxy resin, wherein the modified diamond nanosheets comprise cerium salt-modified diamond nanosheets.
[0013] The modified diamond nanosheet epoxy composite material according to the embodiment of the present invention has at least the following beneficial effects: the present invention modifies the two-dimensional diamond nanosheet by rare earth cerium salt, thereby significantly improving the corrosion resistance of the organic powder coating and ensuring its durability. Specifically, the scheme uses the hydrogen bonds formed between the cerium ions and the abundant hydroxyl functional groups on the surface of the diamond nanosheets and the cation-π interaction to effectively load the cerium ions onto the surface of the diamond nanosheets. This process not only realizes the modification of the diamond nanosheets, but also enables the modified diamond nanosheets to simultaneously exhibit the dual capabilities of physical shielding effect and corrosion inhibition when combined with the epoxy anti-corrosion composite material. The physical shielding effect mainly comes from the fact that the diamond nanosheets are ultra-thin materials with atomic thickness. Their unique two-dimensional structure can construct a complex internal structure similar to a "maze" in the coating, effectively extending the path for the corrosive medium to penetrate into the substrate, thereby enhancing the protective performance of the coating. The corrosion inhibition ability benefits from the introduction of rare earth cerium ions, which can effectively slow down the electrochemical reaction process of the metal substrate in the corrosive medium, further delaying the degradation and failure of the coating.
[0014] The composite material of the present invention not only does not destroy the bonding strength between the epoxy resin and the substrate, but after the cerium salt-modified diamond nanosheets are added to the epoxy resin, the functional groups on the surface can interact with the functional groups on the epoxy resin molecular chain to form a stronger interface bonding force. Therefore, the coating made of the composite material of the present invention can show good bonding strength with the substrate and long-term anti-corrosion performance.
[0015] As an ultra-thin material with atomic-level thickness, two-dimensional diamond nanosheets not only inherit the excellent physical properties of diamond, such as high hardness and high strength, but also show extraordinary performance due to their unique two-dimensional structure. When these nanosheets are introduced into the organic powder coating system, they can build a complex and dense "maze effect" structure inside the coating, which greatly enhances the coating's ability to block corrosive media, so that the corrosive media need to go through a longer path and more obstacles during the penetration process, thereby effectively extending the service life of the composite material.
[0016] In addition, when traditional organic resins face the challenge of corrosive media penetrating into the surface of metal substrates, the acceleration of electrochemical reactions often leads to rapid diffusion of corrosion products, which in turn accelerates the damage and failure of the coating. The present invention, by introducing diamond nanosheets modified with rare earth cerium salts, not only enhances the physical barrier effect of the composite material, but also can exert the corrosion inhibition effect of rare earth cerium ions when potential damage occurs to the metal substrate, effectively slowing down or preventing the electrochemical corrosion process of the metal, thereby further improving the overall corrosion resistance and protective effect of the coating.
[0017] In summary, the scheme of the present invention achieves a significant improvement in the corrosion resistance of organic resin materials through scientific and reasonable modification strategies and structural designs, and provides new ideas and approaches for the development of long-lasting protective coatings.
[0018] According to some embodiments of the present invention, the cerium salt is supported on the diamond nanosheets.
[0019] According to some embodiments of the present invention, the mass ratio of the cerium salt to the diamond nanosheets is 1:1-4.
[0020] According to some embodiments of the present invention, the mass ratio of the modified diamond nanosheets to the epoxy resin is 0.1 to 10:100.
[0021] According to some embodiments of the present invention, the mass ratio of the modified diamond nanosheets to the epoxy resin is 0.5 to 10:100.
[0022] According to some embodiments of the present invention, the mass ratio of the modified diamond nanosheets to the epoxy resin is 1 to 5:100.
[0023] Just adding a small amount of modified diamond nanosheets can significantly improve the corrosion resistance of the composite material, and at the same time, it can also improve the hardness of the composite material.
[0024] According to some embodiments of the present invention, the epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, and epoxy novolac resin.
[0025] According to some embodiments of the present invention, the epoxy resin is Sinopec 804U epoxy resin.
[0026] According to some embodiments of the present invention, the diamond nanosheets are prepared by a chemical vapor method.
[0027] According to some embodiments of the present invention, the diamond nanosheets are undoped or boron-doped diamond nanosheets. Doped (such as B, etc.) or undoped diamond nanosheets can be used.
[0028] According to some embodiments of the present invention, the cerium salt is selected from at least one of cerium sulfate, cerium nitrate or cerium chloride.
[0029] According to some embodiments of the present invention, the raw material further includes a curing agent.
[0030] According to some embodiments of the present invention, the curing agent includes at least one of a dicyandiamide curing agent, a phenol curing agent or an acid anhydride curing agent.
[0031] According to some embodiments of the present invention, the curing agent is CA400 curing agent produced by Sinopec.
[0032] According to some embodiments of the present invention, the mass ratio of the curing agent to the epoxy resin is 10-50:100.
[0033] According to some embodiments of the present invention, the raw material further includes an auxiliary agent.
[0034] According to some embodiments of the present invention, the auxiliary agent includes at least one of a leveling agent, a brightener or a degassing agent.
[0035] According to some embodiments of the present invention, the mass ratio of the auxiliary agent to the epoxy resin is 2 to 10:100.
[0036] The preparation method according to the second aspect of the present invention comprises the following steps:
[0037] S1. Preparation of modified diamond nanosheets: mixing a diamond nanosheet aqueous dispersion with a cerium salt, and reacting the mixture to obtain modified diamond nanosheets;
[0038] S2, mixing the modified diamond nanosheets with other raw materials to obtain.
[0039] The preparation method according to the embodiment of the present invention has at least the following beneficial effects: the preparation process of the scheme of the present invention is not only simple and efficient, but also extremely environmentally friendly, achieving a perfect combination of rapid preparation and green production. The scheme abandons the use of organic solvents and toxic chemical reagents that may be involved in the traditional preparation process, fundamentally avoiding the pollution that these substances may cause to the environment and the potential threat to the health of operators, and successfully responds to the country's green environmental protection policy without sacrificing production efficiency and product quality.
[0040] Specifically, this preparation scheme ensures that the entire preparation process does not rely on any harmful chemicals through carefully designed steps and condition control, thereby effectively reducing the environmental burden of the production process. This transformation not only meets the current urgent need for sustainable development worldwide, but also actively responds to the country's green environmental protection policies and vividly reflects the practice of corporate social responsibility. Through continuous technological innovation and process optimization, the present invention is committed to promoting the development of related industries in a more green, environmentally friendly and sustainable direction, and contributing to the construction of an ecologically civilized society.
[0041] According to some embodiments of the present invention, the reaction conditions in step S2 include: stirring at 300-400 rpm for 3±1 h at a water bath temperature of 25±5°C, and then centrifuging at a speed of 10000±1000 rpm for 15±5 min to obtain a modified nano-diamond precipitate to obtain a modified nano-diamond powder.
[0042] According to some embodiments of the present invention, the reaction conditions in step S2 include: stirring at 350 rpm for 3 hours at a water bath temperature of 25°C, then centrifuging at 10,000 rpm for 15 minutes to obtain a modified nanodiamond precipitate, and drying to obtain a modified nanodiamond sheet.
[0043] According to some embodiments of the present invention, the diamond nanosheets are prepared by CVD equipment, and gas is injected under vacuum conditions to deposit diamond nanosheets on a silicon wafer, comprising the following steps:
[0044] S01, preparation, equipment parameters include: when injecting gas, control the gas pressure to 30±3Toor, power to 1200±120W, substrate temperature to 800±80℃, time to 30±3min;
[0045] S02, nucleation, equipment parameters include: methane flow rate 10-40sccm, hydrogen flow rate 190±19sccm, gas pressure 16±1.6Toor, power 800±80W, substrate temperature 800±80℃, bias -(150±15)V, nucleation time 12±1.2min;
[0046] S03, growth, equipment parameters include: methane flow rate 1 ~ 10sccm, hydrogen flow rate 300±30sccm, gas pressure 30±3Toor, power 1200±120W, substrate temperature 850±85℃, deposition time 1200±120min;
[0047] S04, peeling, crushing and grading.
[0048] According to some embodiments of the present invention, the diamond nanosheets are prepared by CVD equipment, and gas is injected under vacuum conditions to deposit diamond nanosheets on a silicon wafer, comprising the following steps:
[0049] S1. Preparation. Equipment parameters include: when injecting gas, the pressure is controlled to be 30Toor, the power is 1200W, the substrate temperature is 800℃, and the time is 30min.
[0050] S2, nucleation, equipment parameters include: methane flow rate 10sccm, hydrogen flow rate 190sccm, gas pressure 16Toor, power 800W, substrate temperature 800℃, bias voltage -150V, nucleation time 12min;
[0051] S3, growth, equipment parameters include: methane flow rate 1.5sccm, hydrogen flow rate 300sccm, gas pressure 30Toor, power 1200W, substrate temperature 850℃, deposition time 1200min.
[0052] According to some embodiments of the present invention, the specific operation of step S4 includes peeling off the diamond film from the silicon wafer with tape, placing it in a ball mill for crushing, the ball mill speed is 800±100r / min, the ball milling time is 4±1h, and grading and screening to obtain diamond nanosheets.
[0053] According to some embodiments of the present invention, the specific operation of step S4 includes peeling the diamond film from the silicon wafer with an adhesive tape, placing it in a ball mill for crushing, the ball mill speed is 800r / min, and the ball milling time is 4h. Then, the diamond nanosheets are obtained by grading and screening.
[0054] According to the application of the third aspect of the embodiment of the present invention, a coating is provided, wherein the raw materials for preparing the coating include the above-mentioned composite material.
[0055] According to some embodiments of the present invention, the coating is in powder form.
[0056] According to the application of the third aspect of the present invention, a method for preparing a coating is also proposed, comprising the following steps: extruding the composite material through a twin-screw extruder and crushing the composite material to obtain the coating.
[0057] After tableting, crushing, grinding and screening, it is processed into powder state.
[0058] According to the application of the third aspect of the embodiment of the present invention, a method for preparing a coating is also proposed, comprising the following steps:
[0059] The coating is obtained by electrostatically spraying the coating onto the surface of the substrate, solidifying and cooling.
[0060] According to some embodiments of the present invention, the parameters of the electrostatic spraying include: the electrostatic voltage is 60kV to 70kV, the distance between the spray gun nozzle and the metal substrate is 10cm to 20cm, the powder spraying angle is 70° to 90°, and the powder spraying pressure is 0.4MPa to 0.7MPa.
[0061] According to some embodiments of the present invention, the parameters of the electrostatic spraying include: an electrostatic voltage of 60 KV, a distance between the spray gun nozzle and the metal substrate of 15 cm, a powder spraying angle of 90°, and a powder spraying pressure of 0.5 MPa.
[0062] According to some embodiments of the present invention, the curing is thermal curing, and the curing conditions include: a curing temperature of 160° C. to 200° C.; and / or a curing time of 5 to 15 min.
[0063] According to some embodiments of the present invention, the curing is thermal curing, and the curing conditions include: a curing temperature of 180° C.; and / or a curing time of 10 min.
[0064] According to some embodiments of the present invention, the cooling is natural cooling.
[0065] The modified diamond nanosheet / epoxy anti-corrosion composite material is sprayed onto the surface of the metal substrate by electrostatic spraying technology, and then baked and cured, and cooled to obtain the modified diamond nanosheet / epoxy anti-corrosion powder coating.
[0066] According to the application of the embodiment of the third aspect of the present invention, a metal product is also proposed, including a metal substrate and a coating supported on the metal substrate, wherein the raw material of the coating includes the above-mentioned coating.
[0067] According to some embodiments of the present invention, the metal substrate includes steel materials such as carbon steel and other metal or alloy substrates.
[0068] Since the paint, coating and metal product of the present invention contain / adopt the composite material prepared by the above-mentioned preparation method, they have the same technical characteristics as the composite material described in any of the above items and can achieve the same technical effects, and will not be described in detail here.
[0069] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 The scanning electron microscope images of the diamond nanosheets before modification used as raw materials in the examples and comparative examples of the present invention are as follows: (a) low magnification and (b) high magnification.
[0071] Figure 2 The Raman test results of the diamond nanosheets before modification used as raw materials in the examples and comparative examples of the present invention are shown.
[0072] Figure 3 The XRD test results of the diamond nanosheets before modification used as raw materials in the examples and comparative examples of the present invention are shown.
[0073] Figure 4 The corrosion performance test results of Example 2 of the present invention and the comparative example in 3.5wt% NaCl solution are shown.
[0074] Figure 5 1 is a comparison chart of the anti-corrosion mechanism of conventional coating (a) and coating (b) in the embodiment of the present invention. DETAILED DESCRIPTION
[0075] The following will be combined with the embodiments to clearly and completely describe the concept of the present invention and the technical effects produced, so as to fully understand the purpose, characteristics and effects of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of them. Based on the embodiments of the present invention, other embodiments obtained by technicians in this field without creative work are all within the scope of protection of the present invention. The test methods used in the embodiments are conventional methods unless otherwise specified; the materials, reagents, etc. used, unless otherwise specified, can be reagents and materials obtained from commercial channels. Unless otherwise specified, the same parameter in each embodiment has the same value. The embodiments described below are exemplary and are only used to explain the present invention, and cannot be understood as limitations on the present invention.
[0076] In the description of the present invention, the description with reference to the term "some embodiments" or the like means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0077] In the description of the present invention, if there is a description of first, second, etc., it is only for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.
[0078] The preparation process of the diamond nanosheets used in the following examples and comparative examples is as follows:
[0079] The silicon wafer substrate cleaned with ethanol and acetone was placed on a molybdenum substrate table and placed in a CVD device. After vacuuming to below 10-5Pa, the surface of the silicon wafer was cleaned with hydrogen plasma to remove the surface oxide layer and impurities. At this time, the gas pressure was 30Toor, the power was 1200W, the substrate temperature was 800℃, and the time was 30min. Then the diamond nanosheet nucleation stage began. At this time, the specific CVD parameters were: methane flow rate 10sccm, hydrogen flow rate 190sccm, gas pressure 16Toor, power 800W, substrate temperature 800℃, bias voltage -150V, and nucleation time 12min. Finally, the growth parameters of diamond nanosheets in the CVD device were: methane flow rate 1.5sccm, hydrogen flow rate 300sccm, gas pressure 30Toor, power 1200W, substrate temperature 850℃, and deposition time 1200min.
[0080] The epoxy resin used in the following examples and comparative examples is Sinopec 804U epoxy resin, the curing agent is phenolic curing agent 410M, and the auxiliary agent is benzoin auxiliary agent.
[0081] Example 1
[0082] This example provides a modified diamond nanosheet epoxy composite material, which consists of modified diamond nanosheets, epoxy resin, a curing agent and an auxiliary agent. The modified diamond nanosheets are cerium salt modified diamond nanosheets, and the cerium salt is loaded on the diamond nanosheets.
[0083] The specific preparation process is as follows:
[0084] 1) Preparation of modified diamond nanosheets:
[0085] The diamond nanosheets prepared by CVD technology were dissolved in pure water at a concentration of 1g / L and ultrasonically dispersed to obtain a diamond nanosheet aqueous solution. Hexahydrated cerium nitrate was weighed and dissolved in pure water at a concentration of 3g / L to obtain a cerium nitrate solution. The diamond nanosheet aqueous solution and the cerium nitrate aqueous solution were mixed evenly at a total mass ratio of 1:1, and reacted for 3h (magnetically stirred at 350rpm (300-400rpm) at a water bath temperature of 25°C for 3h, and then centrifuged at a speed of 10000rpm for 15min to obtain a modified nanodiamond precipitate, and dried to obtain a modified nanodiamond sheet), and a modified diamond nanosheet solution was obtained. The modified diamond nanosheet solution was centrifuged and dried to obtain a modified diamond nanosheet powder.
[0086] 2) Preparation of composite materials:
[0087] The raw materials are weighed according to the following weight ratio: 100 parts of epoxy resin, 25 parts of curing agent, 0.1 parts of modified diamond nanosheets and 2 parts of auxiliary agent. The raw epoxy resin, curing agent, modified diamond nanosheets and auxiliary agent are mixed evenly to obtain a modified diamond nanosheet / epoxy anticorrosive composite material.
[0088] This example also provides a method for preparing the composite material into a coating, and the specific operation is as follows:
[0089] The product is extruded by a twin-screw extruder, crushed by tabletting, ground and sieved to obtain the product.
[0090] This example also provides a metal product, the preparation process of which is as follows:
[0091] It is electrostatically sprayed onto the carbon steel surface, heat cured and then cooled to obtain the product.
[0092] Specifically, the electrostatic spraying process parameters are as follows: an electrostatic voltage of 60KV, a distance of 15cm between the spray gun nozzle and the metal substrate, a powder spraying angle of 90°, and a powder spraying pressure of 0.5MPa; after being cured by high-temperature baking at 180°C for 10 minutes and then naturally cooled, a modified diamond nanosheet / epoxy anti-corrosion powder coating can be obtained on the surface of the metal substrate, thereby producing a metal product.
[0093] Example 2
[0094] This example provides a modified diamond nanosheet epoxy composite material, which is composed of modified diamond nanosheets, epoxy resin, curing agent and auxiliary agent, and the modified diamond nanosheets are cerium salt modified diamond nanosheets, and the cerium salt is loaded on the diamond nanosheets. The difference between this example and Example 1 is that the quality of the modified diamond nanosheets is different.
[0095] The specific preparation process is as follows:
[0096] 1) Preparation of modified diamond nanosheets:
[0097] The diamond nanosheets prepared by CVD technology were dissolved in pure water at a concentration of 1 g / L and ultrasonically dispersed to obtain a diamond nanosheet aqueous solution. Cerium nitrate hexahydrate was weighed and dissolved in pure water at a concentration of 3 g / L to obtain a cerium nitrate solution. The diamond nanosheet aqueous solution and the cerium nitrate aqueous solution were mixed uniformly at a mass ratio of 1:1 and reacted for 3 hours to obtain a modified diamond nanosheet solution. The modified diamond nanosheet solution was centrifugally dried to obtain a modified diamond nanosheet powder.
[0098] 2) Preparation of composite materials:
[0099] The raw materials are weighed according to the following weight ratio: 100 parts of epoxy resin, 25 parts of curing agent, 1 part of modified diamond nanosheets and 2 parts of auxiliary agents. The raw materials epoxy resin, curing agent, modified diamond nanosheets and auxiliary agents are mixed evenly, extruded by a twin-screw extruder, crushed by tabletting, ground and sieved to obtain a modified diamond nanosheet / epoxy composite material.
[0100] This example also provides a method for preparing the composite material into a coating, and the specific operation is as follows:
[0101] The product is extruded by a twin-screw extruder, crushed by tabletting, ground and sieved to obtain the product.
[0102] This example also provides a metal product, the preparation process of which is as follows:
[0103] It is electrostatically sprayed onto the carbon steel surface, heat cured and then cooled to obtain the product.
[0104] Specifically, the electrostatic spraying process parameters are as follows: an electrostatic voltage of 60KV, a distance of 15cm between the spray gun nozzle and the metal substrate, a powder spraying angle of 90°, and a powder spraying pressure of 0.5MPa; after being cured by high-temperature baking at 180°C for 10 minutes and then naturally cooled, a modified diamond nanosheet / epoxy anti-corrosion powder coating can be obtained on the surface of the metal substrate, thereby producing a metal product.
[0105] Example 3
[0106] This example provides a modified diamond nanosheet epoxy composite material, which is composed of modified diamond nanosheets, epoxy resin, curing agent and auxiliary agent, and the modified diamond nanosheets are cerium salt modified diamond nanosheets, and the cerium salt is loaded on the diamond nanosheets. The difference between this example and Example 1 is that the quality of the modified diamond nanosheets is different.
[0107] The specific preparation process is as follows:
[0108] 1) Preparation of modified diamond nanosheets:
[0109] The diamond nanosheets prepared by CVD technology were dissolved in pure water at a concentration of 1 g / L and ultrasonically dispersed to obtain a diamond nanosheet aqueous solution. Cerium nitrate hexahydrate was weighed and dissolved in pure water at a concentration of 3 g / L to obtain a cerium nitrate solution. The diamond nanosheet aqueous solution and the cerium nitrate aqueous solution were mixed uniformly at a mass ratio of 1:1 and reacted for 3 hours to obtain a modified diamond nanosheet solution. The modified diamond nanosheet solution was centrifugally dried to obtain a modified diamond nanosheet powder.
[0110] 2) Preparation of composite materials:
[0111] The raw materials are weighed according to the following weight ratio: 100 parts of epoxy resin, 25 parts of curing agent, 5 parts of modified diamond nanosheets and 2 parts of auxiliary agent. The raw materials epoxy resin, curing agent, modified diamond nanosheets and auxiliary agent are mixed evenly, extruded by a twin-screw extruder, crushed by tabletting, ground and sieved to obtain a modified diamond nanosheet / epoxy anticorrosion composite material.
[0112] This example also provides a method for preparing the composite material into a coating, and the specific operation is as follows:
[0113] The product is extruded by a twin-screw extruder, crushed by tabletting, ground and sieved to obtain the product.
[0114] This example also provides a metal product, the preparation process of which is as follows:
[0115] It is electrostatically sprayed onto the carbon steel surface, heat cured and then cooled to obtain the product.
[0116] Specifically, the electrostatic spraying process parameters are as follows: an electrostatic voltage of 60KV, a distance of 15cm between the spray gun nozzle and the metal substrate, a powder spraying angle of 90°, and a powder spraying pressure of 0.5MPa; after being cured by high-temperature baking at 180°C for 10 minutes and then naturally cooled, a modified diamond nanosheet / epoxy anti-corrosion powder coating can be obtained on the surface of the metal substrate, thereby producing a metal product.
[0117] Comparative Example
[0118] This example provides a diamond nanosheet epoxy anticorrosive composite material, which is composed of diamond nanosheets, epoxy resin, curing agent and auxiliary agent. The difference between this material and Example 1 is that the diamond nanosheets are not modified.
[0119] The specific preparation process is as follows:
[0120] The raw materials are weighed according to the following weight ratio: 100 parts of epoxy resin, 25 parts of curing agent and 2 parts of auxiliary agent. The raw epoxy resin, curing agent and auxiliary agent are mixed evenly, extruded by a twin-screw extruder, crushed by tabletting, ground and sieved to obtain a two-dimensional diamond nanosheet / epoxy anti-corrosion powder coating, which is electrostatically sprayed on the surface of carbon steel. The electrostatic spraying process parameters are as follows: the electrostatic voltage is 60KV, the distance between the spray gun and the metal substrate is 15cm, the powder spraying angle is 90°, and the powder spraying pressure is 0.5MPa; after curing at 180℃ for 10min and then naturally cooling, a two-dimensional diamond nanosheet / epoxy anti-corrosion powder coating can be obtained on the surface of the metal substrate.
[0121] Test Case
[0122] 1) Morphology and structure testing
[0123] The morphology of diamond nanosheets produced by CVD technology was tested and its morphology was observed by scanning electron microscope images. Figure 1As shown in the figure, the diamond nanosheets have a high aspect ratio and a tiny nano-sized structure (about 70nm in diameter).
[0124] The structure of the diamond nanosheets produced by CVD technology was tested and characterized by Raman spectroscopy and X-ray diffractometer (XRD). Figure 2 As shown. Figure 2 It can be seen that the diamond nanosheets have a -1 There is a characteristic diamond peak at -1 ) is slightly lower than that of the diamond nanosheets, mainly due to the tensile stress in the diamond nanosheets. In addition, it can be seen that the -1 The characteristic peak at , which is mainly related to the graphene sp 2 The XRD characterization results are as follows Figure 3 As shown. Figure 3 It can be seen that there are two obvious peaks corresponding to the (111) and (220) crystal planes of diamond.
[0125] 2) Performance testing
[0126] The metal products prepared in Examples 1 to 3 and the comparative example were subjected to electrochemical corrosion resistance test in 3.5wt% NaCl solution. Furthermore, hardness test was also conducted according to the national standard GB / T 6739-2006 "Determination of paint film hardness by pencil method for paints and varnishes".
[0127] Figure 4 Table 1 shows the results of potentiodynamic polarization curve tests of metal products in Example 2 and Comparative Example. Table 1 shows the results of coating corrosion parameters and hardness tests obtained by Tafel extrapolation method after the potentiodynamic polarization curve test.
[0128] Table 1
[0129] Coating type <![CDATA[Corrosion current density (10 -7 A / cm 2 )]]> Corrosion potential (V) Pencil hardness Example 1 130 -0.48 3H Example 2 5.5 -0.52 4H Example 3 1.4 -0.48 4H Comparative Example 295 -0.36 3H
[0130] from Figure 4 As can be seen from Table 1, the corrosion current density of the metal product made of the two-dimensional diamond nanosheet / epoxy anti-corrosion composite material prepared in Example 2 is significantly lower than that in Comparative Example 1, and the corrosion current density of the metal product made of the two-dimensional diamond nanosheet / epoxy anti-corrosion composite material prepared in Example is significantly lower than that in Comparative Example, which indicates that the composite material of the embodiment has more excellent and lasting corrosion resistance. At the same time, the coatings made using the composite material of the embodiment have a higher pencil hardness.
[0131] The mechanism of action of the composite material of the present invention is speculated to be as follows:
[0132] The polymer coating with barrier protection function can isolate the contact between corrosive media and metal substrate, so as to achieve the protection function for the substrate in a short time. However, there are structural defects such as micropores and cracks inside the coating. During the application process, the corrosive media (water, oxygen, chloride ions, etc.) will penetrate into the metal substrate through the structural defects inside the coating, causing damage and failure of the metal substrate material. The corrosion process of the steel substrate in salt water can be expressed by the following formula:
[0133] Fe-2e - →Fe 2+ (1-1)
[0134] O2+2H2O+4e-→4OH - (1-2)
[0135] Fe 2+ +2OH - →Fe(OH)2 (1-3)
[0136] 4Fe(OH)2+O2+2H2O→4Fe(OH)3 (1-4)
[0137] 2Fe(OH)3→Fe2O3+3H2O (1-5)
[0138] like Figure 5 As shown. After adding cerium salt modified diamond nanosheet filler to epoxy resin, not only can the "maze effect" produced in the coating effectively prevent and delay the penetration of corrosive media due to the two-dimensional layered nanostructure of diamond nanosheets, thereby causing corrosion in a small local area of the substrate interface. Furthermore, through hydrogen bonding and cation-π interactions, the cerium ions loaded on the diamond nanosheet structure will diffuse to the corrosion area when in contact with the corrosive solution and participate in the corrosion reaction, among which Ce 3+ It can react with OH generated at the cathode reaction site - Combined, the reaction (1-3) is blocked, thereby inhibiting the overall corrosion reaction. The process can be expressed by the following formula:
[0139] Ce 3+ +3OH - →Ce(OH)3(1-6)
[0140] 4Ce(OH)3+O2+2H2O→4Ce(OH)4(1-7)
[0141] Ce(OH)4→CeO2+2H2O(1-8)
[0142] The generated CeO2 and Ce(OH)4 can participate in the formation of a uniform, complete, dense and stable mixture deposition film covering the cathode reaction site, thereby further blocking the continuous penetration of corrosive media such as water and oxygen, so that the corroded area is more durably protected, and produce a synergistic effect with the physical barrier protection function of the diamond nanosheets. Therefore, the cerium salt modified diamond nanosheet epoxy composite coating in the present invention has long-term anti-corrosion performance.
[0143] Compared with the traditional method of using CeO2 to coat diamond powder to form a core-shell structure, the packing mechanism proposed in the present invention is completely different. In the present invention, diamond is processed into a nanosheet structure. This two-dimensional layered structure can naturally form a physical barrier, effectively delaying or preventing the penetration of corrosive media. In contrast, the traditional method usually uses spherical or irregular diamond powder. Furthermore, the innovation of the present invention lies in the use of CeO2 to coat diamond powder. 3+ The Ce 3+ Ce is firmly loaded on the layered surface of diamond nanosheets. This design not only makes full use of the physical barrier properties of the diamond nanosheet layer structure, but also when the corrosive medium tries to invade the interior of the coating, the Ce loaded on the nanosheet layer 3+ Can actively participate in corrosion reactions. Specifically, Ce 3+ The OH produced at the cathode reaction site - Combined, thereby inhibiting the progress of the overall corrosion reaction. This reaction will generate CeO2 and Ce(OH)4, which will be deposited at the site of corrosion to form a dense, stable and complete reaction barrier film. This film can further completely block the corrosion medium from invading the substrate material and significantly improve the corrosion resistance of the epoxy coating. Therefore, the mechanism of the present invention is fundamentally different from the mechanism of the traditional CeO2-coated diamond powder to form a core-shell structure.
[0144] The solution of the present invention adds modified diamond nanosheets to the organic epoxy resin system, which not only significantly improves the corrosion resistance, but also the composite material of the solution of the present invention shows good bonding strength with the substrate, and has a long-lasting anti-corrosion effect. At the same time, the addition of modified diamond can also improve the adhesion of the coating, enhance the stability of the coating when it is impacted, and improve the friction and wear performance of the coating, so that the coating can maintain a more durable and reliable protection effect under complex and changeable environmental conditions. The present invention modifies the diamond nanosheets by introducing corrosion inhibitors and then applies them to organic coatings. This innovative strategy not only gives the coating additional corrosion inhibition properties, but also further enhances the overall anti-corrosion performance of the organic coating. During the application process, once the corrosive medium penetrates into the surface of the metal substrate, the traditional organic coating will rapidly diffuse the corrosion products through electrochemical reactions, thereby accelerating the damage or even failure of the coating. The coating with the composite material of the solution of the present invention can effectively inhibit the electrochemical reaction of the metal after the metal substrate is damaged, thereby inhibiting the damage of the metal material.
[0145] The two-dimensional diamond nanosheet of the present invention is an atomic-thin diamond nanosheet with unique physical properties, and has multiple excellent properties of diamond. Therefore, when it is added to the organic powder coating system, it can construct an internal structure with a "maze effect", which is conducive to extending the channel for the penetration of corrosive media, thereby creating a protective organic coating with light weight, high strength and long-term corrosion resistance. Diamond nanosheets with high aspect ratio and nanometer particle size are accurately prepared by chemical vapor deposition (CVD) technology. These nanosheets show unique performance advantages due to their extremely small microscopic size, and can effectively improve the corrosion resistance of epoxy powder coating under the premise of significantly reducing the amount of addition, and can also enhance the mechanical strength and wear resistance of the coating to a certain extent. The preparation process of the modified diamond nanosheet / epoxy anti-corrosion composite material involved in the present invention has the characteristics of short process and fast operation. At the same time, the whole preparation process is green and environmentally friendly, and the use of organic solvents and toxic chemical reagents is completely abandoned, actively responding to and practicing the green environmental protection policy advocated by the country.
[0146] In summary, the present invention adds a trace amount of modified diamond nanosheet filler to epoxy resin powder, which can enhance the corrosion resistance of the coating through the physical barrier effect. Diamond nanosheets are modified with environmentally friendly green rare earth cerium salts to further give the organic coating a corrosion inhibition effect. The scheme of the present invention not only provides a new idea and technical path for the development of high-performance anti-corrosion coatings, but also makes a positive contribution to promoting the development of environmentally friendly coatings.
[0147] The embodiments of the present invention are described in detail above, but the present invention is not limited to the above embodiments. Various changes can be made within the knowledge scope of ordinary technicians in the relevant technical field without departing from the purpose of the present invention.
Claims
1. A modified diamond nanosheet epoxy composite material, characterized in that: The invention comprises the following raw materials: modified diamond nanosheets and epoxy resin, wherein the modified diamond nanosheets comprise cerium salt modified diamond nanosheets.
2. The modified diamond nanosheet epoxy composite material according to claim 1, characterized in that: The cerium salt is supported on the diamond nanosheets; preferably, the mass ratio of the cerium salt to the diamond nanosheets is 1:1-4.
3. The modified diamond nanosheet epoxy composite material according to claim 1, characterized in that: The mass ratio of the modified diamond nanosheets to the epoxy resin is 0.1 to 10:100; preferably, the mass ratio of the modified diamond nanosheets to the epoxy resin is 0.5 to 10:
100.
4. The modified diamond nanosheet epoxy composite material according to claim 1, characterized in that: The epoxy resin includes at least one of bisphenol A epoxy resin, bisphenol F epoxy resin, and epoxy novolac resin; and / or the diamond nanosheets are undoped or boron-doped diamond nanosheets; and / or the cerium salt is selected from at least one of cerium sulfate, cerium nitrate, and cerium chloride.
5. The modified diamond nanosheet epoxy composite material according to claim 1, characterized in that: The raw materials also include a curing agent, and the curing agent includes at least one of a dicyandiamide curing agent, a phenolic curing agent or an acid anhydride curing agent; preferably, the mass ratio of the curing agent to the epoxy resin is 10-50:
100.
6. The modified diamond nanosheet epoxy composite material according to claim 1, characterized in that: The raw materials further include an auxiliary agent, and the auxiliary agent includes at least one of a leveling agent, a brightener or a degassing agent; preferably, the mass ratio of the auxiliary agent to the epoxy resin is 2 to 10:
100.
7. The method for preparing the modified diamond nanosheet epoxy composite material according to any one of claims 1 to 6, characterized in that: The steps include: S1. Preparation of modified diamond nanosheets: mixing a diamond nanosheet aqueous dispersion with a cerium salt, and reacting the mixture to obtain modified diamond nanosheets; S2, mixing the modified diamond nanosheets with other raw materials to obtain.
8. The preparation method according to claim 7, characterized in that: The diamond nanosheets are prepared by CVD equipment, and gas is injected under vacuum conditions to deposit diamond nanosheets on silicon wafers, including the following steps: S01, preparation, equipment parameters include: when injecting gas, control the gas pressure to 30±3Toor, power to 1200±120W, substrate temperature to 800±80℃, time to 30±3min; S02, nucleation, equipment parameters include: methane flow rate 10-40sccm, hydrogen flow rate 190±19sccm, gas pressure 16±1.6Toor, power 800±80W, substrate temperature 800±80℃, bias -(150±15)V, nucleation time 12±1.2min; S03, growth, equipment parameters include: methane flow rate 1 ~ 10sccm, hydrogen flow rate 300±30sccm, gas pressure 30±3Toor, power 1200±120W, substrate temperature 850±85℃, deposition time 1200±120min; S04, peeling, crushing and grading to obtain.
9. A coating, characterized in that: The raw materials for preparing the coating include the composite material according to any one of claims 1 to 6.
10. The coating according to claim 9, characterized in that: The coating is in powder form.
11. A method for preparing a coating, characterized in that: The method comprises the following steps: extruding the composite material as claimed in any one of claims 1 to 6 through a twin-screw extruder, and crushing the composite material to obtain the composite material.
12. A method for preparing a coating, characterized in that: The steps include: The coating is obtained by electrostatically spraying the coating as claimed in claim 9 or 10 onto the surface of a substrate, curing and cooling.
13. A metal product, characterized in that: The invention comprises a metal substrate and a coating layer supported on the metal substrate, wherein the raw material of the coating layer comprises the coating material as claimed in claim 9 or 10.
14. The metal product according to claim 13, characterized in that: The metal substrate includes carbon steel.
Citation Information
Patent Citations
Wear-resisting powder coating
CN105482627A
Cerium salt modified graphene / epoxy powder coating as well as preparation and application thereof
CN117946563A
Fluorinated diamond nanosheet anticorrosive coating and preparation method thereof
CN118048061A
Soft-hard combined low-surface-energy 2D diamond nanofiller as well as preparation method and application thereof
CN118684940A
Thermal insulation coating, preparation method therefor and application method thereof
WO2023082911A1